How South Korean Celebrities Affect Consumer Behavior: A Study of Purchase Intent Factors in Iran - Gholami, Samira (Universitas Airlangga, 2025)
The Korean Wave attracted many tourists to South Korea, generating high revenues through the entertainment industry . The popularity of Korean media influenced food culture, hairstyles, make-up type, beauty standards and coating style . In Iran, the wave also partially penetrated . Beautiful actors and singers became popular with the public, which led many manufacturers to work in the field of Korean food production, Korean restaurant construction and Korean fashion . In recent years there were a number of South Korean immigrants from Iran. Due to the popularity of the entertainment industry, many Iranian immigrants living in Korea offer Korean entertainment, cosmetics and food products through social networks and are selling them, although in Iran, Korean products are not represented due to sanctions. In this study, I looked at the indicators that affect the sale of Korean goods, and after looking at the effectiveness and absence of each, I ranked one using multiple regression . Five main factors were ultimately identified, with celebrity popularity ranking first, followed by the celebrities' physical attractiveness, and the third priority being that the celebrities be actual consumers of the advertised product . The fourth priority was about celebrity credibility and The fifth and final priority is to match the celebrity with the advertised product.